An Analysis of Big 4 Pricing and Firm Size: The Differential Impact of Demand and Supply Shocks on Large and Small Clients. (April 2019) - Alali, Fatima; Elder, Randal; Zhou, Jian
We investigate Big 4 pricing over the period of 2000 to 2010. We classify the data into five periods: 2000-2001 as the pre-Sarbanes–Oxley Act (SOX) period, 2002-2003 as the SOX period, 2004-2006 as the Auditing Standard 2 (AS2) period, 2007 as the AS5 period, and 2008-2010 as the Great Recession period. The shocks to the audit market associated with these changes in auditing regulations and the economic environment have differential impacts on large clients and small clients. The percentage of small clients using Big 4 auditors dropped significantly over these shocks, whereas the percentage of large clients using Big 4 auditors experienced a large drop only from the SOX period to the AS2 period. We find that Big 4 pricing increased significantly from the pre-SOX period to the SOX period and continued to increase significantly in the AS2 period. Big 4 pricing experienced a significant decline in the AS5 period and declined insignificantly in the Great Recession period. Big 4 small firm pricing decreased significantly in the AS2 period compared with the SOX period and in the Great Recession period compared with the AS5 period. We find that the Big 4 pricing for small clients is contingent on the nature of competition. The Big 4 charged small firms higher prices in the SOX period, AS5 period, and Great Recession period when competition was lower. Our paper provides a unique contribution as a comprehensive analysis of Big 4 pricing and Big 4 small firm pricing.